Cancer Diagnoses during Active Conflict: Experience from a Cancer Program in Northwest Syria - Atassi, Bassel; Tse, Gina; Mkhallalati, Hala; Debel, Jamil; Jemmo, Ayham; Khalil, Molham; Alrahal, Yahya; Almalki, Monzr; Hamadeh, Mufaddal; Tarakji, Ahmad; Abbara, Aula (Avicenna Journal of Medicine, 2022)
Background Protracted conflict has destroyed Syria's health system with severe impacts on the diagnosis and treatment of chronic and high-cost diseases including cancer. Here, we review the type and (where possible) the stage of cancers diagnosed in a pathology laboratory serving Northwest Syria.Methods We retrospectively reviewed all pathology reports which reported a diagnosis of cancer from a pathology department in Northwest Syria from January to December 2020.Results A total of 397 new cancers were diagnosed during 2020 of which 191 were among males (48.1%) and 20 cases were in children aged 17 years or under (5%). The most common cancer in men was bladder cancer (15.7%) and skin cancers (14.7%) followed by cancers in the lymph nodes (includes primary and secondary; 9.9%.) In women, breast cancer (38.3%) followed by skin cancer skin (9.7%) and uterine cancer (8.7%) was the most common. The overall proportion of cancer diagnoses were breast cancer (20.2%), skin cancer (12.1%), cancer affecting lymph nodes (8.8%), and urinary bladder (8.3%) and colorectal cancer (7.3%).Discussion This preliminary analysis is the first report of cancer types and demographics in areas outside of government control in Syria since the onset of the conflict. Despite limitations, it presents some indication of the burden of oncological diagnoses in this area. Further research which aims to describe and address the burden of cancer on populations under ongoing conflict and humanitarian crises remains essential, especially in Northwest Syria given ongoing attacks and severe underfunding. There is a particular need to investigate how best to apply interventions and support health systems and cancer services within conflict settings. More support and resources need to be allocated to cancer centers with long-term health partnership models. The underresourced and understaffed conditions of the hospital are significant limits to a more detailed report.
Keywords: cancer; Syria; conflict; histopathology; breast cancer